Revisiting Feminist Strategies in Poetry: Gender, Genre, and Power Relation - A.B. Sri Mulyani (Journal of Language and Literature, 2022)
The patriarchal gender division of private-public dichotomy assigned to particular gender for different roles and sphere is generally viewed as an “ancient” practice in the West. However, this “ancient” gender conception that can be traced from its Greco-Roman and Judeo-Christian roots can frequently be pertinently visible in modern Western world as exemplified in the notion of “Woman’s place” and; it becomes the dominant gender discourse. Consequently, this discourse continually creates hierarchical and unequal power relation that marginalizes women in accessing education and their full participation in public spheres. This limited accessibility to education (including language and literacy) also shapes the roles and status of women as writers in Western critical and literary tradition.  Writing as a profession is traditionally men’s domain; therefore, the production and contribution of women writers have less privilege and space in the Western canon. Women writers from time to time have to struggle to reclaim their rights and place in it. This research attempts to re-examine how this (re)production of the binary opposition of private-public sphere operates in language and literature of the Western critical literary tradition by scrutinizing the selected poems by the selected women writers in this research. Furthermore, this research also studies and locates how women writers employ particular strategies in gendering and degendering their writings as both aesthetic and ideological expressions. In conclusion, this research argues that women writings are not “deficient” and “inferior” to their male counterpart; and instead their status and difference as writers are the result of patriarchal dominance and power relation that historically have subordinated and denied them equal public access to education, language, literacy, and literary production.